Early Brain MRI Predicts Outcome of Term HIE - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2011)
Researchers at Hammersmith Hospital, London, UK, studied the accuracy of early brain MRI for predicting death, the presence and severity of motor impairment, and ability to walk at 2 years in 175 term infants treated for hypoxic-ischemic encephalopathy (HIE) in the period 1993 to 2007.